UPAYA GURU DALAM MENGATASI KEJENUHAN PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP AL-IHSAN YAPIS KOTARAJA - Irianto, Ilham; Firdaus, Muh. Anang; Yaqin, Husnul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Some of the problems underlying the learning saturation experienced by students at SMP Al-Ihsan Yapis Kotaraja Such as the discomfort in the room, the teacher's lack of interest in teaching, and the material being given, which is not enjoyable. This problem cannot be overcome if it is only limited to the way of teaching that is evaluated but must also pay attention to the atmosphere remaining conducive and attracting student learning interest. This research is a qualitative descriptive study with a phenomenological approach. The data collection method uses observation, interviews, and documentation from PAI teachers, school principals, and two students. The results of this study indicate that in order to overcome the saturation of the PAI learning process, the school works together between PAI subject teachers and homeroom teachers at Al-Ihsan Middle School to provide examples of religious values and create an interesting learning atmosphere such as games or competition so they don't get bored with learning PAI.